Occupational ergonomics risk factors prioritization using integrated analytical hierarchy process (AHP) approach: a study of a local automotive component manufacturer - Fazilah, Abdul Aziz; Z., Ghazalli; N. M. Zuki, N. M. (Human Factors and Ergonomics Society Malaysia (HFEM), 2019)
There is a need to support the occupational safety and health (OSH) practitioners defining their priorities action for improving working environment condition and minimizing the risk factors in the early stage of development. This paper aims to identify the critical risk factors of occupational ergonomics among production workers in an automotive component manufacturer. The Analytic Hierarchy Process (AHP) was utilized to prioritize the level of four ergonomics risk main factors and 26 sub-factors. The linear interpolation and a probability value were given by the practitioner to identify the magnitude of risk. In conclusion, physical factors (0.3143) and psychosocial factors (0.2920) were ranked as the two most important risks of occupational ergonomics. The main effective sub-factors initiating occupational ergonomics risk were found that include force exertion in job task (15), carrying and lifting the heavy load (13.91), high workload (13.04) and work stress (11.89). The simple and systematic approach for occupational ergonomics risk factors analysis should help managers of safety and health, as well as production to conduct ergonomics intervention programs that meet workers’ needs and enhance productivity. Such prioritization helps organizations to prioritize their ergonomics intervention practices on job task thereby increasing the preventive strategies and proactively reducing the occupational ergonomics risk factors.